Kinetics of Phase Transformation of Indium in the Presence of Polytetrafluoroethylene: Implications for DSC Measurements on Polymers and Their Composites. (25th May 2015) - Raimo, Maria
Abstract : The present work focuses on the influence, at nominal constant temperatures, of an inert polymer on the crystallization kinetics of a highly conductive metal as indium (In) to show not only that the presence of a polymer allows obtaining information on the In crystallization directly from differential scanning calorimeter (DSC) curves, but also that appropriate corrections of thermal measurements on low conductivity samples are needed.